Managing Workforce Diversity in Organization: A Case Study on Aetna Health Care Service - Khan, MD. Rahat; Shobikah, Nanik; Kaium, Mohammad Abdul (The Pontianak State Institute of Islamic Studies, 2020)
The impact of globalization is nothing new to the business firms. In the last few decades globalization has changed the business strategies of the companies. The current case study has tried to evaluate the Aetna’s diversity approaches named ‘The Aetna Way’ policy along with its complexity of implementation in people management issues. The report is categorized as follows. The first part of the report has discussed about the background of investigation. The following part has analyzed some closely related literatures related to the context. This past basically narrate the theme of recruitment and retention policy along with talent management process and its significance for the company. The third part of the case has assessed the Aetna’s recruitment and retention policies and then tried to compare the Aetna’s policies with close competitors’ and top performing companies’. This part also evaluates Aetna talent management process and policies and also compare with the competitors. After that in fourth part, the study points some recommendations with justification. The study has recommended the Aetna, to change the traditional recruitment policy and give more concentration on employee retention rate. Technology driven talent management practices should be the time worthy policy of the Aetna. Focusing more on LAMP and MCC frameworks would enhance the effectiveness and efficiency in recruitment, retention, and talent management policies for the Aetna.